Disain & Simulasi Rangkaian Pengatur Tegangan AC Enam Fasa Dengan Beban Resistif - effendi, effendi; Fitriady, Fitriady (Politeknik Aceh, 2023)
Power electronics is a field that studies electronics applications related to electrical equipment that uses large amounts of power, one of the subject that studied is AC to AC converters. AC voltage regulator is a converter where the output frequency is the same as the input frequency of the voltage sources, while the RMS output voltage can be regulated. In this research the number of phases that used are six phases, and two SCRs that used to chopper the AC voltage wave that arranged it in revers for each phase.The control circuit is constructed by using an op-amp which functions as a comparator and several other basic electronic components. the simulation results that using PSIM software for several delay angles including 30o, 60o, 90o, 120o, and 150o produce rms voltage that is relatively the same as the analysis by using mathematically calculations, this difference is because the SCR gate delay angle is still done manually, in general the voltage regulator The six-phase AC in this study can work well.